If it's not what You are looking for type in the equation solver your own equation and let us solve it.
1/3x+1=1/6(2x+3)
We move all terms to the left:
1/3x+1-(1/6(2x+3))=0
Domain of the equation: 3x!=0
x!=0/3
x!=0
x∈R
Domain of the equation: 6(2x+3))!=0We calculate fractions
x∈R
(6x2/(18x^22+(-(1*3x)/(18x^22+1=0
We do not support expression: x^22
| 8=d+5/4 | | -3x+4+5x=4x-12 | | 6p-22=2+2p | | 5x^2=-19x-12 | | 11=x/3+5 | | F(x+1)=4x^2+2x-3 | | 3x2-15x=-7 | | 14-x=17-5x | | 26=8+.25x | | 3x2-15=-7 | | k-3÷=10 | | 26=8+3/4x | | -12u=-24 | | k-3÷4=10 | | 2x+46=6x+6 | | -29=-v/5 | | 1/x+3/x-5=15/x(x-5) | | f(-2)=3+5(-2)+2(-2)^2 | | 3x2-17x+10=0 | | 11y=8-9+6y | | X(4)=2+x | | 60/y=4 | | n+15(n-1)=7 | | 10,691-257x=8328 | | 14-2x=x+2 | | 4y-8-y=10y-3y | | -4+4n=2n-4-3n | | 3=w/5-15 | | 6x-28=180 | | 6^2−2x+1=0 | | x^2-7x/6-1/3=0 | | 3-y=5y+y |